P0119 PTEN expression affects outcome of human hepatocellular carcinoma via modulation of the oncogenic phenotypes and angiogenic processes. (July 2015) - Tseng, P.-L.; Lin, P.-R.; Tai, M.-H.; Huang, C.-C.; Wang, C.-C.; Lin, J.-W.; Wang, J.-H.; Lee, C.-M.; Chang, K.-C.; Yen, Y.-H.; Tsai, M.-C.; Lin, M.-T.; et al.
Abstract : Background: Reduced PTEN expression is associated with overexpression of VEGF in various malignancies. We aimed to investigate the expression of PTEN and VEGF and their association in the development of hepatocellular carcinoma. Findings: PTEN expression was reduced in 43% and VEGF was overexpressed in 31% of 113 resected hepatocellular carcinoma clinical specimens. VEGF overexpression is positively correlated with young age, male sex, hepatitis B viraemia, high α -fetoprotein levels, reduced PTEN expression, advanced stage hepatocellular carcinoma, and hepatocellular carcinoma dedifferentiation. Survival analysis revealed that reduced PTEN expression, microvessel density, and advanced tumour stage were independent poor prognostic factors for disease-free survival. Adenovirus-mediated restoration of PTEN -inhibited cell proliferation, clonogenic growth and invasive capability of PTEN-deficient human hepatocellular carcinoma cells in vitro . In a xenograft animal model of hepatocellular carcinoma, PTEN gene delivery could efficiently suppress the incidence and growth rate of implanted tumour cells and reduce microvessel density. Decreased expression of angiogenic-associated factors, including VEGF, IL-8, and HIF1 α, was found in PTEN-restored hepatocellular carcinoma cells in vitro . Angiogenic networks of human umbilical vein endothelial cells were also suppressed by the increased PTEN expression. Interpretation: These results show that tumour microenvironment can be affected by PTEN expression through modulation of the oncogenic phenotypes of tumour cells and a tendency to interfere in angiogenic processes. In conclusion, expression of PTEN and VEGF affecting the outcome of human hepatocellular carcinoma might serve as good prognostic biomarkers.